Uptake of Climate Smart Agriculture in Peri-Urban Areas of South Africa's Economic Hub Requires Up-Scaling - Chitakira, Munyaradzi; Ngcobo, Nombuso Z. P. (Frontiers in Sustainable Food Systems, 2021)
Climate variability and change impact significantly on food security and the livelihoods of smallholder farmers making it necessary for the farmers to prioritise investment in adaptation and mitigation approaches, such as climate smart agriculture, to enhance resilience. Climate smart agriculture approaches have been adopted in many countries around the world to address the adverse impacts of climate change on agricultural production. There is limited information about climate smart agriculture adoption by peri-urban farmers in developing countries. The present study aimed to assess the extent to which agricultural activities by smallholder crop farmers in the City of Tshwane Metropolitan Municipality in Gauteng province of South Africa are climate smart, and to establish the sustainable measures to be put in place to enhance the adoption of climate smart agriculture. The study made use of a mixed method design combining qualitative and quantitative approaches. A combination of simple random and non-probability sampling techniques was employed to select the study locations and identify respondents. A sample of thirty-six farmers were selected for the study. The main findings revealed overwhelming awareness of climate change and the impacts thereof on crop productivity and yields. However, the respondents’ level of awareness of climate smart agriculture technologies was generally low. Despite the lack of knowledge of climate smart agriculture practices, the farmers were, to an extent, utilising adaptation mechanisms acquired from indigenous systems or scientific knowledge. Examples of these practices include mulching, cover cropping, crop rotation and use of crop varieties. The study concludes that much more can be done to scale up the uptake of climate smart agriculture in the Gauteng province. The study recommends formal and informal strategies including one-on-one extension programs to raise the awareness of climate smart agriculture technologies appropriate to the unique conditions of the farmers.